Three Levels of Disease Modification with SGLT-2 Inhibitors: Holy Grail in Vasculopathy - Archit Dhaiya; Rajeev Sharma; Nagendra Bhoopathy; Rajeev Agarwal (RUHS Journal of Health Sciences, 2023)
SGLT2 inhibitors have an insulin-independent mechanism of action leading to increasing glycosuria and lowering plasma glucose concentration, which results in cardiovascular and renal benefits shown in various studies. Other benefits include improvements in hyperglycemia, decreased fluid retention, reduced weight gain, lower blood pressure, and decreased risk of hypoglycemia. SGLT2 inhibitors produce cardioprotective and renoprotective benefits by inducing a state of Fasting Mimicry. It is therefore noteworthy that SGLT2 inhibitors induce a transcriptional paradigm that closely mimics the cellular response to starvation. These drugs activate SIRT1/AMPK and suppress Akt/mTOR signaling and, consequently, they can promote autophagy, independent of their effects on glucose or insulin. SGLT2 inhibitors regulate the expression of MicroRNA and prevent the occurrence and development of atherosclerosis, and can improve blood vessel stiffness and aging.